Reader-Response Study on Characteristics of Arafo Women in Nodeko’s Web Manga Dokushin OL No Tatemae To Honne - Dewi Puspitasari; Eka Marthanty Indah Lestari (Bina Nusantara University, 2018)
This research aimed to analyzed the responses of readers regarding the characteristics of Arafo women in web manga. In this case, the researchers want to see the responses of the readers regarding occupation, marriage, and the lifestyle of Arafo women. With the reception theory by Hall, it could be seen whether the message from the author of the web manga about Arafo women can be fully understood or interpreted differently by the readers. This research used a qualitative method with the research steps; namely identifying the suitable respondents, planning the instruments in the form of the list of questions for an interview, collecting data through field study (related to interview), and literature review (related to the written data). Data analysis was performed with stages; namely processing the result of the interview, reducing data, grouping data, interpreting data, and concluding data. The research result shows that there are three types of readers based on the theory of Hall; namely dominant/hegemonic position regarding age and occupation of Arafo women, the negotiated position related to issue of independence, and oppositional position related to issues of spouse and marriage. Different feedbacks from the readers on the same text are affected by some factors; namely knowledge about the condition of Japanese society and Arafo women, a difference of experience, and difference of perspective.